Science and education: modern trends - Lysenko E. M., Iantser O. V., Astafeva O. A., Koloskova T. A., Kapustina O. V., Shabaev V. G., Solovev V. V., Savinov A. M., Builova L. N., Builova L. N., Kargina Z. A., Karimova L. A., Komutstsi L. V., Sungatullina A. O., Shamtieva M. R., Badashkeev M. V., Sofronova N. I., Sofronov G. A., Bokova O. A., Volokhov S. P., Shamarina E. V., Zhdanova S. N., Dolgova V. M., Popova T. N., Maslennikova D. I., Pavlova V. S., Ermakova I. A., Gogolin V. A., Efremova L. I., Grigorash O. V., Efimova S. A., Kravec A. V., Zykov M. B., Kirpicheva M. A., Magomedova G. M., Skoblikova T. V., Skripleva E. V., Gorokhov V. F. (Science and education: modern trends, 2015)
this paper considers the modern methodology and analyzes the methodological approaches of research sphere of additional education for children, clarified the interpretation of the pedagogical phenomenon, compared definitions given by theorists and practitioners, refined understanding of the new roles of additional education of children in modern Russian education system.
Keywords: дополнительное образование детей; методология; индивидуальное развитие ребенка; мотивация к познанию; мотивация к творчеству; свобода выбора; базовая дефиниция; контекстуальная дефиниция; методологическое основание; методологический подход; additional education of children; methodology; methodological approach; indi-vidual development of the child; the motivation for learning; the motivation for creativity; freedom of choice; the basic definition; contextual definition; methodo-logical basis